Compliance with the Municipal Agro-Environmental Legislation in Francisco de Orellana, Ecuador - E. Pozo; J. Pozo; A. Bonilla; J. Jimenez (ESPOCH Congresses)
The Decentralized Autonomous Municipal Government of the Francisco de Orellana canton is made up of the following rural parishes: Alejandro Labaka, Armenia, Dayuma, El Dorado, El Edén, García Moreno, Guayusa, Inés Arango, La Belleza, Nuevo Paraiso, Taracoa and the Urban Parish of El Coca. The Constitution of the Republic of Ecuador (2008) establishes the rights of nature and protects the biodiversity of the Amazon ecosystem. This is complemented by the provisions of the Organic Code of Territorial Organization, Autonomy and Decentralization (2010), the Organic Code of the Environment (2017) and also the Organic Law for the Integrated Planning of the Special Amazon Territorial District (2018). This article reviewed compliance with municipal agro-environmental legislation in the Decentralized Municipal Autonomous Government of the Francisco de Orellana canton. This analysis was based on the publication of the Organic Law for the Integrated Planning of the Special Territorial District of the Amazon in the Official Registry Supplement 245, dated May 21, 2018. A qualitative methodology was used. Data were collected through analysis of public policies, regulations, legislation and ordinances, and interviews with the main actors of the Decentralized Municipal Autonomous Government. The results suggested that the Municipal Government seeks to protect the biodiversity of the Amazon ecosystem by adopting sustainable development and conservation policies, but it is clear that ordinances are needed for agro-environmental education, garbage classification, recycling, organic gardens, and greater integration into municipal agro-environmental projects.